Isolation and Identification of Bacteria from Urinary Tract Infections - Noor Hamid Abbas Al- Marzoog; Heba Saleh Shaheed; Alaa Yousif Oudah (Institute of Medico-legal Publications Pvt Ltd, 2021)
A urinary tract infection (UTI) is an infection in any part of urinary system (kidneys, ureters, bladder and urethra). Most infections involve the lower urinary tract, the bladder and the urethra. Women are at greater risk of developing a UTI than are men. In this study, (50) urine sample were collected from (50) patients with suspected urinary tract infection, during the period from December (2017) to March (2018). The results of this study revealed that (70%) of samples was positive for bacterial culture, while (30%) of sample have no growth. The bacterial culture shown that (18) (51.43%) of bacterial isolates was E. coli followed by Staphylococcus aureus (8) (22.86%) and Klebsiella spp (17.14%) (6) , Proteus spp .(8.57%) (3). In-vitro, the susceptibility of bacteria towards some antibiotics included in this study revealed that the Ciprofloxacin, Gentamicin, and Chloramphenicol are the most effective antibiotics to different types of pathogenic bacteria.